Exposure of salivary gland cells to low-frequency electromagnetic fields alters polypeptide synthesis. - Goodman, R (1988)
This study demonstrates that exposure of cells to extremely low-frequency electromagnetic fields can cause measurable changes in protein synthesis. Sciara coprophila salivary gland cells were exposed to five low-frequency (1.5-72 Hz) electromagnetic signals: three signals (1.5, 15, and 72 Hz) produced pulsed asymmetric electromagnetic fields and two signals (60 and 72 Hz) were sinusoidal. Subsequent analyses of two-dimensional gels showed that cell exposure to either type of low-frequency electromagnetic field resulted in both qualitative and quantitative changes in patterns of protein synthesis. Thus, signals producing diverse waveform characteristics induced previously undetectable polypeptides, some of which were signal specific and augmented or suppressed other polypeptides as compared with nonexposed cells. The pattern of polypeptide synthesis differed from that seen with heat shock: only five polypeptides in cells exposed to electromagnetic signals overlap those polypeptides exposed to heat shock, and the suppression of protein synthesis characteristic of heat shock does not occur.